2016
DOI: 10.3390/su8020178
|View full text |Cite
|
Sign up to set email alerts
|

Does Land Tenure Security Promote Manure Use by Farm Households in Vietnam?

Abstract: Abstract:Facing widespread poverty and land degradation, Vietnam started a land reform in 1993 as part of its renovation policy package known as "Doi Moi". This paper examines the impacts of improved land tenure security, via this land reform, on manure use by farm households. As manure potentially improves soil fertility by adding organic matter and nutrients to the soil surface, it might contribute to improving soil productive capacity and reversing land degradation. Random effect regression models are appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…It was discovered that fixed renters and sharecroppers faced problems to get credit which lead to reduced investment. Nguyen, Bauer [9] asserted that the accessibility of credits explicitly depends on the security prerequisites from institutional sources or indirectly rely on the priority of the protected borrower-owner. Almost all landlords who received institutional loans in the survey area used land as security, which highlights the importance of land as guarantee for institutional credit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was discovered that fixed renters and sharecroppers faced problems to get credit which lead to reduced investment. Nguyen, Bauer [9] asserted that the accessibility of credits explicitly depends on the security prerequisites from institutional sources or indirectly rely on the priority of the protected borrower-owner. Almost all landlords who received institutional loans in the survey area used land as security, which highlights the importance of land as guarantee for institutional credit.…”
Section: Discussionmentioning
confidence: 99%
“…Shaban [5] claimed that shared leases are likely to reduce inputs and productivity by 32% and 16%, respectively. Nguyen, Bauer [9] discovered that enhancing land investment affected tenure security significantly upon assessing the impact of secure land rights and investment on agriculture within the context of Thailand. Lovo [10], in the context of Malawi, reported that soil conservation was positively affected by secure ownership rights.…”
Section: Introductionmentioning
confidence: 99%
“…During the Civil War from 1954 to 1975 and the subsequent time period after the unification, there was a scarcity of food due to several reasons, including inefficient operation of state-owned agricultural cooperatives and ineffective institutional arrangements, such as land tenure [49]. The country started its renovation policy package known as 'Doi Moi' in 1986 and since then has achieved rapid economic growth [50].…”
Section: Case Study: Consumption and Production Of Meat In Vietnammentioning
confidence: 99%
“…Therefore they mainly focus on the social and economic dimensions, whereas environmental aspects are only treated as cross-cutting topics or an unequal dimension. Some sustainability assessments that focus on the long-term effectiveness of benefits do not consider additional negative or positive impacts within the social, economic and environmental dimension [43]. Other methods take into account all three pillars of sustainability but in an unbalanced way by giving the social dimension more weight or by not using quantifiable indicators [25,[44][45][46].…”
Section: State-of-the-art and Challengesmentioning
confidence: 99%